The role of moderate to vigorous physical activity level and number of treatments/medications in mediating the effect of body mass index on diabetic nephropathy: a Mendelian randomization study - Shasha Hu; Yuling Chen; Mingjie He; Jun Wen; Aimin Zhong; Dandan Zhan; Zhibin Ye (Renal Failure)
Background Body mass index (BMI) is associated with diabetic nephropathy (DN). However, the mediator factors in the BMI-DN effects remain unclear.Methods Univariate and multivariate Mendelian randomization (MR) analysis were performed to estimate the association between six lifestyles (moderate to vigorous physical activity levels, years of schooling, BMI, nap during day, number of treatments/medications taken and coffee intake) and DN. MR Egger, Weighted median, Simple mode, and Weighted mode was supplemental methods to Inverse variance weighted. Sensitivity analysis included heterogeneity test, horizontal pleiotropy test, and Leave-One-Out. Additionally, mediation MR was conducted to evaluate the mediating role of lifestyles between BMI and DN. Finally, functional enrichment analysis based on the mediation MR results was performed.Results univariate and multivariate Mendelian randomization (MR) analysis were performed to estimate the association between six lifestyles (moderate to vigorous physical activity levels, years of schooling, BMI, nap during day, number of treatments/medications taken and coffee intake) and DN. MR Egger, Weighted median, Simple mode, and Weighted mode was supplemental methods to Inverse variance weighted. Sensitivity analysis included heterogeneity test, horizontal pleiotropy test, and Leave-One-Out. Additionally, mediation MR was conducted to evaluate the mediating role of lifestyles between BMI and DN. Finally, functional enrichment analysis based on the mediation MR results was performed.Conclusion our results supported mediation role of vigorous physical activity level and number of treatments/medications in BMI-DN effects.